Over the Atlantic : Diplomacy and Paradiplomacy in EU and Latin America. - Astroza Suarez, Paulina; Laschi, Giuliana; Oddone, Nahuel; Torres Jarrin, Mario (Brussels : P.I.E. - Peter Lang SA Éditions Scientifiques Internationales, 2023)
The book analyses diplomacy and paradiplomacy in the European Union and in Latin America from a multidisciplinary perspective. The paradiplomacy, as a means of unofficial relationships that reacts differently to the pressure of the international system, despite its relevance and importance, is scarcely analysed by academia.
Cover -- Series Information -- Copyright Information -- Table of contents -- Introduction (Paulina Astroza Suarez, Giuliana Laschi, Nahuel Oddone, Mario Torres Jarrin) -- Part I: The institutionalization and normalization of paradiplomacy in foreign policy in Latin America and Europe -- Cross-border paradiplomacy in Latin America: Opportunities and challenges for the reopening of borders and the post-Covid-19 recovery (Nahuel Oddone) -- The international linkage of Chilean regions as an example of paradiplomacy in a Unitary State (Paulina Astroza Suárez, Pablo Navarro Rosas) -- Galician paradiplomacy (1981-2021): A general description and ten final notes (Celso Cancela Outeda) -- Part II: Paradiplomacy and cooperation, between international and regional relations -- Link between the localization of SDGs and territorial development: An environmental paradiplomacy-based approach (Mariano Alvarez) -- Paradiplomacy, "actorness", and the global agendas (Javier Sánchez Cano) -- Paradiplomacy and cooperation in the pandemic era: A review from China in Latin America (Florencia Rubiolo, Gonzalo Fiore Viani) -- Part III: Beyond traditional state diplomacy: Cities and parliaments as international diplomatic actors -- Parliamentary diplomacy in practice: The role of the European Parliament delegations in the modernization of the Global Agreement between the European Union and Mexico (Mónica Velasco-Pufleau) -- City diplomacy. Theory and practice of paradiplomacy: Smart city Sweden case (Mario Torres Jarrín).
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books